1989
DOI: 10.3109/10641968909035359
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Atrial Natriuretic Factor in Normal Pregnancy and Early Puerperium

Abstract: The atrial natriuretic factor (ANF) and parameters related to renal sodium handling and renal function were evaluated in 92 normotensive pregnant women at different gestational ages (1st group: 7th-13th week, 2nd group: 14th-20th week; 3rd group: 21st-27th week; 4th group: 28th-34th week; 5th group: greater than 34th week), in 15 normotensive non-pregnant women and in 15 normotensive women 6 days after spontaneous delivery at the end of a normal pregnancy. ANF did not differ significantly between the 5 groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…However, in the 5-72 h of the late postpartum period, the plasma level of ANP declines significantly from that in the immediate post¬ partum period, to the value seen in the third trimester or at term, although the level remains significantly higher than that in the first trimester. Our results agree with the findings of Musoni et al (1988) and Shrivastav et al (1988), but not with those of Rutherford et al (1987), Steegers et al (1987, Malatino et al (1988) or Marlettini et al (1989), all of whom report a significant increase in plasma ANP during the 3-to 5-day postpartum period compared with the concentration in late pregnancy. The plasma level of BNP continues to rise during the late postpartum period compared with the immediate postpartum period, when the concentration significantly exceeded that at term pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…However, in the 5-72 h of the late postpartum period, the plasma level of ANP declines significantly from that in the immediate post¬ partum period, to the value seen in the third trimester or at term, although the level remains significantly higher than that in the first trimester. Our results agree with the findings of Musoni et al (1988) and Shrivastav et al (1988), but not with those of Rutherford et al (1987), Steegers et al (1987, Malatino et al (1988) or Marlettini et al (1989), all of whom report a significant increase in plasma ANP during the 3-to 5-day postpartum period compared with the concentration in late pregnancy. The plasma level of BNP continues to rise during the late postpartum period compared with the immediate postpartum period, when the concentration significantly exceeded that at term pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that plasma ANF levels return to non-pregnant values near term is in agreement with previous data from rats (Castro et al 1989) and humans (Otsuki et al 1987;Steegers et al 1991), but is nonetheless surprising since circulating blood volume is greatly expanded at this time (Barron, 1987) and is associated with significant atrial distension, at least in humans (Steegers et al 1991). It is generally agreed that postpartum levels of ANF are significantly elevated in both the human and the rat (Nadel et al 1988;Castro et al 1989;Jansakul et al 1989;Marlettini et al 1989); our data are in agreement with these findings. It has been suggested that high circulating ANF levels contribute to the pronounced natriuresis and diuresis observed during the postpartum period (Nadel et al 1988;Gregoire et al 1990).…”
Section: Discussionsupporting
confidence: 82%
“…1988, Jackson et al . 1988, Marlettini et al . 1989), the postulated links between the gradual gestational increase in intravascular volume, atrial stretch and ANP release have not been made clear.…”
mentioning
confidence: 99%